A study of higher education students attitudes towards learning the prganizational foundations of glaukoma treatment and prevention (Environment & Health, 2026)
The Aim. To investigate the need among future doctors of various specialties (students of medical universities) to study the fundamentals of diagnosis, treatment, and prevention of glaucoma.Materials and Methods. The research tool was a self-developed questionnaire. The study materials consisted of data obtained from a survey of senior students at three medical universities in Ukraine. Bibliographic, statistical, and analytical methods were used.Results. Overall, 80% of medical students believe that knowledge of the discipline Ophthalmology is necessary for future doctors of all specialties. Seventy-five percent of respondents rated the volume and quality of ophthalmology knowledge obtained during their undergraduate training at 3–5 points on a 5-point scale. One-third of students rated their knowledge of the organization of ophthalmic care and the prevention of ophthalmic diseases at 3 points. More than 80% highly valued the importance of understanding modern approaches to organizing glaucoma prevention and the factors influencing its development for doctors of all specialties. While most future doctors recognize the need to know the modern algorithm of actions in cases of suspected glaucoma or pseudoexfoliative syndrome, not all consider in-depth knowledge of modern glaucoma treatment approaches to be necessary. Although 75% of students plan to apply knowledge of glaucoma prevention in their future practice, they do not plan to engage in specific preventive activities aimed at preventing its development.Conclusions. In general, 70–80% of surveyed medical students recognize the importance of knowledge in ophthalmology. However, their evaluation of the volume and quality of the knowledge they acquired was not sufficiently high. Future doctors are aware of the importance of understanding risk factors for glaucoma and its prevention, while assessments of the need for in-depth knowledge of modern treatment approaches and the organization of glaucoma prevention were more reserved. Sixth-year medical students and interns feel uncertain about their theoretical and practical ophthalmology knowledge. Ophthalmology educators should clearly demonstrate the importance of ophthalmological knowledge for various specialists, especially family physicians.
Keywords: ophthalmology; glaucoma; education; medical students; specialties; awareness; risk factors; early diagnosis; prevention